2015
DOI: 10.1088/1674-1137/39/12/123102
|View full text |Cite
|
Sign up to set email alerts
|

An updated study of ϒ production and polarization at the Tevatron and LHC

Abstract: Following the nonrelativistic QCD factorization scheme, by taking latest available measurement on χ b (3P ) into consideration, we present an updated study on the yield and polarization of Υ(1S, 2S, 3S) hadroproduction, and the fractions of χ b (mP ) feed-down in Υ(nS) production at QCD next-to-leading order. In the fitting, three schemes are applied with different choice of χ b (mP ) feed-down ratios and NRQCD factorization scale. The results can explain the measurements on yield very well as in our previous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(102 citation statements)
references
References 45 publications
6
96
0
Order By: Relevance
“…The corresponding values are listed in tables 2-4. By integrating the double-differential results over p T (y), the differential cross-sections times dimuon branching fractions as functions of y (p T ) are shown in figure 3 for the three Υ states, with the theoretical predictions based on NRQCD [24] overlaid. The NRQCD predictions are in agreement with the experimental data at high p T .…”
Section: Cross-sectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding values are listed in tables 2-4. By integrating the double-differential results over p T (y), the differential cross-sections times dimuon branching fractions as functions of y (p T ) are shown in figure 3 for the three Υ states, with the theoretical predictions based on NRQCD [24] overlaid. The NRQCD predictions are in agreement with the experimental data at high p T .…”
Section: Cross-sectionsmentioning
confidence: 99%
“…Statistical and systematic uncertainties are added in quadrature. Predictions from NRQCD [24] for the Υ (1S) (black grid shading), Υ (2S) (red grid shading) and Υ (3S) (blue grid shading) states are overlaid in the top plot.…”
Section: Jhep07(2018)134mentioning
confidence: 99%
See 1 more Smart Citation
“…The larger mass, higher scale and lower velocity could make the Υ a better candidate for an accurate description by NRQCD. In addition, since there are more Υ states, there are more color octet LDMEs available for fitting, allowing a description of the p T -dependent yields and the polarization simultaneously [33,[51][52][53][54].…”
Section: Quarkonium Productionmentioning
confidence: 99%
“…On the side of theory the maturation of effective field theory frameworks, such as NRQCD [17], systematically derived from Quantum Chromo Dynamics (QCD), have made it possible to compute many of the properties of heavy quarkonium in concert either with perturbation theory or lattice QCD simulations. And indeed both the J/Ψ polarization puzzle at Tevatron [18][19][20] and the challenges associated with reproducing polarization effects in hadroproduction of Υ states at LHC have revealed that a thorough understanding of finite angular momentum bound states in vacuum is essential for charmonium [21,22] as well as bottomonium [23,24]. The experimental studies showed on the one hand that the feed-down from χ b (3P ) to Υ(3S), formerly disregarded in theory, can be sizable, while on the other hand the theory computations themselves concluded that e.g.…”
Section: Introductionmentioning
confidence: 99%